PENGARUH PERBEDAAN KONSENTRASI KARAGENAN TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK JELLY DRINK PEPAYA - Vania, Jovica; Utomo, Adrianus Rulianto; Trisnawati, Chatarina Yayuk (Jurnal Teknologi Pangan dan Gizi, 2017)
Characteristics of jelly drink are have soft gel so that when consumed using a straw, gel will break easily, but the gel form is still felt in the mouth. Those characteristics can be achieved by adding gelling agent, which is carrageenan. The concentration of carrageenan will affects on the stability and gel characteristics of jelly drink. This research is aimed to determine the effect of difference carrageenan concentration on the physicochemical and sensory properties of papaya jelly drink and determine the right carrageenan concentration that obtain the most preferred papaya jelly drink by panelists. This research used Randomized Block Design with one factor, which was concentration of carrageenan (P), which consisted of six levels, 0.1% (P1); 0.125% (P2); 0.15% (P3); 0.175% (P4); 0.2% (P5); 0.225% (P6) with four replications. Analysis for physicochemical properties were syneresis, easiness to sucked, and pH and sensory properties were preference of easiness consumed using straw, mouthfeel, and taste. The result of papaya jelly drink’s analysis showed that higher carrageenan concentration caused declined on syneresis, while on easiness to sucked and pH parameter are increased. Best concentration of carrageenan determined by the result of organoleptic using spiderweb method is adding jelly drink with 0,150% of carrageenan which had results during storage for 1,4, and 7 days respectively on syneresis (14,96%; 9,56%; 5,62%), easiness to sucked (12,44; 11,04; 10,17), pH (4,65; 4,56; 4,51) with average of organoleptic on easiness consumed using straw 5,02; mouthfeel 4,96; and taste 4,68 with score of 1-7.